Дослідження сформованості пізнавальних процесів у дітей п’ятого року життя із ЗНМ - Брушневська, Ірина; Brushnevska, I. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті автор представляє результати експериментального дослідження сформованості пізнавальних процесів, а саме сприймання та уваги різних модальностей, у дітей п’ятого року життя із загальним недорозвитком мовлення (ЗНМ). Аналізує і характеризує виявлені механізми порушень, вказує на їх взаємообумовленість. Зазначає, що порушення алгоритму цілісного зорового сприймання дітей, обмеженість слухової уваги та слухового контролю, що є причиною порушення слухового сприймання, є однією із причин недостатньої сформованості мовленнєвої діяльності у дітей п’ятого року життя із ЗНМ. Вказує, що характерними особливостями уваги дітей є порушення функціональності процесів довільної зорової уваги, недостатня концентрація на суттєвих ознаках, порушення довільної слухової уваги. На основі отриманих результатів буде розроблено зміст методики формування комунікативного компонента у дітей п’ятого року життя із ЗНМ. The author of this article presents the results of the experimental research in cognitive processes development, namely perception and awareness of five years old children with GSI (General Speech Impairment). She analyzes and characterizes the violation mechanisms and indicates their interdependence. The author notes that the auditory attention limitation and the auditory control limitation can cause the hearing impairment and can be one of the reasons of insufficient speech development of five years old children with GSI. The study the main components of the children’s speech activity are of a great importance at the present stage of the special pre-school pedagogy development. Scientists use the latest scientific data about the psycholinguistic structure of speech activity, its psychological mechanisms. The child's perception processes of different modalities (auditory, visual, tactile, kinesthetic, olfactory, gustatory) are closely connected with thinking, understanding the essence of the object and are characterized by selectivity, which allows to select one item despite the short-term influence of other irritants. We examined the perception in the visual and auditory modalities, due to their priority for sound diferencian formation underlying in speech activity and the spoken language formation at the earliest stages of child’s development. Sound as an object of auditory perception is based on a clear communication focus.
The research in the development of cognitive processes of five years old children with GSI
Keywords: мовленнєва діяльність; дошкільники; сприймання; увага; загальний недорозвиток мовлення; звичайний мовленнєвий розвиток; дослідження; speech activity; preschoolers; perception; attention; General Speech Impairment; normal speech development; research